A comprehensive methodology to screen metal-organic frameworks towards sustainable photofixation of nitrogen. (4th January 2021) - Mohamed, Amro M.O.; Bicer, Yusuf
Highlights: An efficient methodology requires molecular modelling to find desired properties. Screening of Hypothetical MOFs showed lack of diversity for N2 photofixation. Zn3 (BTC)2 (C6 H5 ) is a potential candidate for N2 photofixation from the database. Metal substitution and ligand functionalization offer to tune electronic properties. Abstract: Distinct photoactive material compositions have been investigated starting from the mid-70s to reduce energy and pollution associated with ammonia synthesis. Hitherto, photocatalysts suffer from low ammonia yield and incomprehensive understanding of the mechanisms. The target of this research is to develop a systematic and comprehensive approach to screen and design durable and efficient metal-organic frameworks (MOFs) as catalysts to drive the photofixation of nitrogen at atmospheric conditions. This work discusses the available databases in the context of photocatalysis for the first time and reviews essential descriptors by incorporating Quantum Mechanics and molecular simulation techniques, taking into consideration sustainability aspects. As a result of a study on Hypothetical MOFs, Zn3 (BTC)2 (C6 H5 ) has shown to satisfy the requirement for photofixation of nitrogen, using hydrogen and nitrogen as inputs, to ammonia. Comparison between Zn3 (BTC)2 (C6 H5 ) and NH2 -MIL-125(Ti) has been made based on geometrical, bandgap, diffusion coefficients, adsorption properties and life cycle assessment analysis of the production phase. Graphical abstract: Image, graphical abstract